Ferroptosis at the intersection of radiotherapy and immunotherapy - Gui-Xia Wei; Ya-Qin Zhao; Rong Tang; Hua-Shan Shi; Zhi-Ping Li (Cancer and Metastasis Reviews, 2025)

Plantation forest stand age affects the characteristics and the chlorine reactivity of soil-derived dissolved organic matter - Xin-Yi Jiao; Su-Ping Liu; Shuang Peng; Zi-Hao Wu; Fu-Qiang Fan; Le Fang; Yan-Chao Jin; Peng Liu; Cai-Shan Wang; Ding Pan; Xue-Rong Wang; Ying-Zhi Ding; et al. (Water Research, 2025)

Rainfall, seasonal variation, and stream type governing the multi-media fate and ecological risks of tire additives and their transformation products in mega-urban streams - Li-Ni Wei; Nian-Nian Wu; Ru Xu; Yuan Liu; Shan Liu; Hai-Yan Zhang; Zi-Tong Li; Yue-Hong Liu; Xiang-Rong Xu; Jian-Liang Zhao; Guang-Guo Ying (Water Research, 2025)

Integrating the neuro-immune-cancer axis into CAR-T cell therapy: advances and challenges - Yi-Jin Li; Rong Shen; Wei-Li Zhao (Science Bulletin, 2025)

One new rearranged pyranone derivative with antibacterial activity from Xylaria curta YSJ-5 - Shan-Shan Wei; Dao-Jun Rong; Jia-Ying Lai; Chen Chen; Si-Ran Li; Zhong-Hua Yu; Hai-Bo Tan (Phytochemistry Letters, 2025)

Influence of multiple environmental factors on plastics in facility agriculture soils at a national scale, China - Guiming Liu; Sashuang Rong; Cun Liang; Yang Yang; Xuyang Zheng; Shutao Wang; Shiming Su; Zhenyong Li; Wei Liu (Journal of Environmental Chemical Engineering, 2025)

Unravelling the migration of bioactive and volatile compounds coupled with water sublimation from grapes to recovered water during dynamic freeze-drying - Mengru Li; Wei Zhang; Yuan Huang; Xiaoying Zhang; Wuernisha Kadeer; Leihong Mao; Yuqian Jiang; Rong Tsao; Yao Tang (Food Chemistry, 2025)

Development and validation of a magnetic - based corrosion detection system for reinforced concrete structures - Jian Cheng; Yu-meng Xie; Rong-sen Gao; Ye Tian; Guo-yi Zhang; Dongming Yan; Bo Chen; Ruo-yi Zhao; Bei Li; Jun Chen; Dong-yang Cai; Wei-qiang Wu; et al. (Engineering Structures, 2025)

Imidazole-modified separator for uniform polysulfide anchoring and accelerated redox in Li S batteries - Xiangwei Zhao; Qin Dong; Wei Hong; Rong Li; Xinglong Gou; Ruiyi Gan; Tao Wang; Cunpu Li (Chemical Engineering Journal, 2025)

Langmuir/BET ratio as a quantitative indicator: Chain length-dependent adsorption modes of fillers regulating ion transport and high-voltage performance in PEO-based composite electrolytes - Ding Nan; Altan Bolag; Rong Zhang; Ji Qi; Bila Ga; Tana Bao; Wei Li; Lei Li (Chemical Engineering Journal, 2025)

Effects of Optimized Nitrogen Fertilizer Application on Chlorophyll Fluorescence Characteristics and Dry Matter Accumulation in Sugar Beet - Shi-Feng Dong; Lei Wei; Xing-Bo Tong; Yi-Na Zhang; Rong-Li Jia; Xu-Ming Xing; Shu-De Shi (Sugar Tech, 2025)

Satb2 Ablation Impairs Hippocampus-Based Long-Term Spatial Memory and Short-Term Working Memory and Immediate Early Genes (IEGs)-Mediated Hippocampal Synaptic Plasticity - Ying Li; Qiang-Long You; Sheng-Rong Zhang; Wei-Yuan Huang; Wen-Jun Zou; Wei Jie; Shu-Ji Li; Ji-Hong Liu; Chuang-Ye Lv; Jin Cong; Yu-Ying Hu; Tian-Ming Gao; et al. (Molecular Neurobiology, 2025)

IFNGR1, IRF8 genetic polymorphisms modulate the susceptibility of non-tuberculous mycobacteria pulmonary disease and influence the patients’ treatment outcomes and immune status - Li-ping Cheng; Zhi-bin Liu; Lei Wang; Jie Cao; Qing-rong Qu; Hai Lou; Xiao-na Shen; Juan Yang; Yuanyuan Yu; Rui Juan Zheng; Wei Sha; Qin Sun (Inflammation Research, 2025)

Acute systemic inflammation induces region-specific morphological remodeling of astrocytes and microglia concurrent with depression-like behavior - An-Qi Zhang; Meng-Meng Zhang; Ling-Jie Li; Mei-Xue Yuan; Rong-Yu Liu; Peng Chen; Chen-Wei Wang; Yu Wang; Jiang-Ning Zhou; Qing-Hong Shan; Xin-Ya Qin (Histochemistry and Cell Biology, 2025)

WISP2/CCN5 revealed as a potential diagnostic biomarker for endometriosis based on machine learning and single-cell transcriptomic analysis - Sheng Dou; Shaohua Ling; Weihua Nong; Bixiao Wei; Yuehua Huang; Guangjing Li; Rong Wang; Haimei Qin (Functional & Integrative Genomics, 2025)

High-Resolution Three-Pressure Prediction of Lianggaoshan Formation in LT1 Well block of Eastern Sichuan Risk Exploration Area - Yu-wei Wang; Ke-zhen Wan; Rong-rong Zhao; Wen-hao Li; Yang Lin; Hao Long; Hu Zhao (Applied Geophysics, 2025)

Application of ambient noise tomography to coastal granite islands: A case study of Wuzhizhou Island in Hainan, China - Cheng Huang; Sheng Liu; Jun-Qiao Long; Chang-Rong Zhang; Bo Xiao; Da-Cheng Wang; Cheng-Long Wei; Rui Wang; Li Yan; Xuan Hu; Zhuo Xin; Xiu-Ji Meng; et al. (Applied Geophysics, 2025)

Limonoids and protolimonoid from Swietenia macrophylla - Yun-Peng Sun; Wen-Fang Jin; Ze-Rong Xu; Ying-Wei Liu; Li-Juan Sun; Yang Yu; Jin-Song Liu; Guo-Kai Wang (Natural Product Research, 2025)

Carbon stabilization by iron plaque on rice roots: The role of oxygen loss - Liang Wei; Xuechi Rong; Hongzhao Yuan; Yongfu Li; Xiaorong Fan; Ning Ling; Zhenke Zhu; Bahar S. Razavi; Yakov Kuzyakov; Pil Joo Kim; Jianping Chen; Tida Ge (Soil Biology and Biochemistry, 2025)

Biosynthetic rule-guided theoretical chemical space mapping strategy for enhanced analysis of plant metabolomes: application to the geographical profiling of goji berry - Wan-Yang Sun; Zhi-Hui Luo; Jie-Qi Cai; Qian Guo; Guo-Tao Chen; Guo-Dong Chen; Dan Hu; Hai-Guang Gong; Xue Li; Wei Bi; Ying Wang; Kwok-Fai So; et al. (Science Bulletin, 2025)

A BrDof2.4-BrHDA6 module is involved in ABA-CTK-mediating leaf yellowing in Chinese flowering cabbage by affecting histone H3 and H4 acetylation of CCGs - Zhen-liang Mou; Lei Yan; Zong-li Liu; Xin-guo Su; Ze-xiang Zeng; Yuan Rong; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen; Wei Wei; Jia Si (Postharvest Biology and Technology, 2025)

Scandium enrichment in the weathering crust of Emeishan basalt, Dali: geochemical abundance, occurrence states, and pre-concentration potential - Xiaorui Wang; Ruidong Yang; Wei Cheng; Rong Chen; Jun Chen; Xinzheng Li (Minerals Engineering, 2025)

Carbohydrate-metabolizing gastrointestinal bacteria mediate resistome divergence in high feed efficiency Holstein dairy calves - Tianyu Chen; Shangru Li; Jianxin Xiao; Rong Peng; Mo Sha; Jingjun Wang; Jiaying Ma; Wei Wang; Mei Ma; Shengli Li; Zhijun Cao; Shuai Liu (Journal of Hazardous Materials, 2025)

Hydrothermal carbonization: A potent strategy for simultaneously eliminating ARGs-associated pollutants in livestock manure and blocking ARGs horizontal gene transfer - Sunlin Chi; Jinmei Xiao; Jinying Xu; Aijing Li; Jianhui Hu; Xinyi Wang; Meiyan Zhang; Wei Liu; Yalan Zhang; Huijun Ding; Jun Rong; Li Leng; et al. (Journal of Hazardous Materials, 2025)

Residue carbon and C-degradation gene indicated the increase of soil organic carbon following vegetation restoration on the Loess Plateau, China - Rong Wang; Shicai Li; Yixian Ruan; Runhao Shi; Hongjian Hao; Yujie Liang; Ahejiang Sailike; Zhouchang Yu; Rong Fu; Ning Peng; Xinhui Han; Wei Zhang; et al. (Journal of Environmental Management, 2025)

A biodegradable cellulose-based ionic conductor for sustainable and high-safety quasi-solid-state sodium batteries - Yuejing Zeng; Rong Tang; Minghui Chen; Yaqi Zhang; Wei Li; Huiya Yang; Ruilai Ye; Xue Li; Yang Yang; Jinbao Zhao (Chemical Engineering Journal, 2025)

Crystal facet optimization in cadmium sulfide/reduced graphene oxide-based photosynthetic biohybrid systems for enhanced light-driven biohydrogen production - Xue-Meng Wang; Zhi-Xuan Zhang; Lin Chen; Rong Chen; Wen-Wei Li (Bioresource Technology, 2025)

ZxSAUR15 regulates root growth and abiotic stress tolerance: from genome-wide characterization of SAUR genes in Zygophyllum xanthoxylum to functional validation - Chunli Liu; Mengzhan Li; Yuting Yang; Rong Chai; Li Wei; Hongju Yin (Plant and Soil, 2025)

The potential role of hydrogen sulfide-autophagy axis in diseases - Ti Chu; Yan-Wen Wang; Lei Cao; Xue-Li Wang; Yong-Qi Fan; Yu-Hang Chen; Yi Zhang; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Journal of Physiology and Biochemistry, 2025)

Three new triterpenoids from the fruit of Eleutherococcus senticosus (Rupr.) Harms - Yan Liu; Yu-Xuan Lin; Xiao-Hui Rong; Meng-Meng Li; Juan Pan; Wei Guan; Hai-Xue Kuang; Bing-You Yang (Natural Product Research, 2025)

Decoupled motion planning method for 7-DOF manipulator and lifting joint in automated tomato harvesting - Jiacheng Rong; Yu Liu; Xianjun Li; Chao Gao; Pengbo Wang; Ting Yuan; Wei Li (Computers and Electronics in Agriculture, 2025)

Carbon dots promote tomato growth and yield via photosynthesis enhancement and leaf senescence delay - Shuang Li; Wenbo Zhao; Wei Zhao; Zhen Jiao; Keqiao Cui; Rong Wang; Aiying Wang; Yuantao Tan; Huandong Li; Yue Yin; Feijuan Gao; Kaikai Liu; et al. (Journal of Plant Physiology, 2025)

Deep eutectic solvent-mediated green synthesis of phosphorylated biomass adsorbents for high-efficient uranium removal from uranium tailings wastewater - Ya Wei Yang; Jie Liu; Jing Huang; Cheng Rong Zhang; Sai Jin Xiao; Xin Xin Shao; Han Wu; Li Zhang (Journal of Environmental Chemical Engineering, 2025)

Interfacial regulation of natural magnetite for oil-water separation in oily petrochemical wastewaters - Rong Wang; Jiarui Du; Junyi Li; Chenyang Zhang; Wei Sun (Journal of Environmental Chemical Engineering, 2025)

Adaptive responses and molecular mechanisms of Lactiplantibacillus plantarum to citric acid stress - Han Xie; Wei Zhang; Cong-Rong Shi; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

DPP-IV inhibitory peptides from highland barley via machine learning and multi-scale validation - Xin Bao; Yiyun Zhang; Liyang Wang; Zijian Dai; Rong Li; Kefan Wei; Jiaqian Cao; Qingyu Zhao; Qun Shen; Yong Xue (Food Chemistry, 2025)

A ZnO packaged MEMS hydrogen sensor for reliable SIBO breath analysis with anti-H2S interference - Zheng Yang; Qian Rong; Wei Zhang; Xintao Fan; Mengen Shao; Jiang Li; Chunchang Wang; Youmin Guo (Chemical Engineering Journal, 2025)

Residual polyacrylamide-induced membrane fouling in short-flow coagulation-ultrafiltration: Behavior and mechanism - Mohan Wei; Yaozhong Zhang; Xing Zheng; Chi Zhang; Jiheng Duan; Kai Guo; Menghan Wang; Dongfei Li; Tianshuo Huang; Rong Chen (Chemical Engineering Journal, 2025)

The development of biological soil crusts shifts the drivers of soil multifunctionality in drylands - Mingming Wang; Boyi Song; Benfeng Yin; Ye Tao; Jing Zhang; Xiaoying Rong; Yonggang Li; Shihang Zhang; Zihan Kan; Yongxing Lu; Hao Guo; Xing Guo; et al. (CATENA, 2025)

Construction of LncRNA-miRNA-mRNA regulatory network in IgA nephropathy mice model by RNA-sequencing and bioinformatics analysis - Wen Jia Zheng; Tao Liu; Xiao Li Zhu; Yu Ting Zhang; Liang Bing Wei; Ya Chen Gao; Xing Xing Zhuang; Jia Rong Gao (Genes & Genomics, 2025)

One-pot construction of monodisperse core-shell silica microsphere with quinine-containing hybrid fibrous shell for racemates separation - Chenyang Wang; Tiantian Guo; Rong Li; Shujuan Ma; Yinmao Wei; Junjie Ou (Analytica Chimica Acta, 2025)

Targeting cuproptosis in liver cancer: Molecular mechanisms and therapeutic implications - Yun-Fei Zhou; Yi-Wen Zhu; Meng-Yuan Hao; Hong-Jie Li; Hang-Shen Han; Yan-Ge Li; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Apoptosis, 2025)

Elucidation of the anti-fibrotic diseases mechanism of chelerythrine by integrative approach of network pharmacology and experimental verification - Wei Han; Gui-yun Qian; Qin-rong Wang; Jie Liu; Yong-ping Zhang; Jian Xu; Tingting Li; Zhe Li (Natural Product Research, 2025)

In vitro physiological and biochemical responses underlying salt tolerance of five turfgrass species - Zhen-Peng Wei; Yu-Ping Xiong; Jaime A. Teixeira da Silva; Jian-Rong Li; Jun-Yu Liu; Yuan Li; Zhan Bian; Xin-Hua Zhang; Guo-Hua Ma (Vegetos, 2025)

Biogenic Cu2-xSe nanoparticles with vacancy engineering quickly upcycle cobalt from wastewater for photothermal antibacterial and desalination - Xue-Meng Wang; Zhi-Xuan Zhang; Yun-Jie Wang; Hao-Yu Li; Wen-Wei Li; Rong Chen (Water Research, 2025)

Regulatory mechanism of microplastics on arsenic bioavailability in a subtropical estuary, China - Yue Zeng; Yajie Jiang; Yunqin Li; Xiang Xu; Rong Yu; Wei Yu; Binxin Wu; Meiling Xiao (Science of The Total Environment, 2025)

Ten eudesmane sesquiterpenoids from Dobinea delavayi and their antimalarial and lipid-lowering activities - Wei Chen; Li-Tian Dong; Pei-Mi He; Wei-Juan Zu; Yi-Ling Yang; Rong Liu; Bei Jiang; Chao-Jiang Xiao (Phytochemistry, 2025)

Anti-neuroinflammatory naphthol dimers from the marine-derived fungus Penicillium sp. HQ1-23 - Yuan-Han Xie; Chun-Hong Wang; Rong Wang; Hui Jia; Fei Liu; Zi-Hong Peng; Ya-Hui Zhang; Jun Li; Rui-Yun Yang; Li-Jun Zhang; Wei-Feng Xu (Phytochemistry, 2025)

Complete genome of Thalassotalea piscium NK451B, an Antarctic bacterium with abundant extracellular proteases - Jia-Yi Song; Zi-Ying Li; Xiao-Hui Yang; Jin-Rong Wei; Kang Li; Yi Zhang (Marine Genomics, 2025)

Evaluation of probiotic properties of lactic acid bacteria and physicochemical characteristics of fermented jujube (Ziziphus jujuba Mill.) polysaccharides - Rong Wang; Shufan Xie; Fei Li; Lanjian Qin; Jianming Ye; Jiaqi Chen; Xiao Yang; Yunlu Wei (Food Bioscience, 2025)

Synergistic electrostatic, coordination, and redox mechanisms in cationic covalent organic frameworks for ultrafast and selective gold recovery - Meng-Yao Zhou; Xiu Wang; Shun-Hao Zeng; Qian-Qian Zhao; Yibao Li; Wei-Rong Cui (Chemical Engineering Journal, 2025)

Beyond convention: Construction of β-cyclodextrin-based shape-changing particles capable of light-responsive control and bioactivity application - Pu-Ying Qi; Li-Hong Shi; Zhi-Cheng Zheng; Yu-Mei Feng; Tai-Hong Zhang; Rong-Shuang Luo; Shuai Tan; A-Ling Tang; Hou-Yun Huang; Xiang Zhou; Hong-Mei Xiang; Li-Wei Liu; et al. (Carbohydrate Polymers, 2025)

Cloning and Bioinformatics Analysis of the StGRAS46 Gene in Potato - Shulin Wang; GuoHong Weng; Rong Zhang; Wei Li; YongJie Bai; YaHui Zhang; JianWu Li (Potato Research, 2025)

Quorum-sensing Inhibitory Activity of Xanthones from Hypericum Curvisepalum N. Robson Against Chromobacterium Violaceum - Hong Zeng; Qiu-Ying He; Sheng-Qiang Yang; Xiao-Lian Wei; Jia-Zi Luo; Jing-Kai Zhou; Rong-Bing Fu; Li-Ping Teng; Zhong-Bo Zhou (Current Microbiology, 2025)

Genetic diversity and population structure of four Trapa species from the Yangtze River and Amur River basins, China - Miriam Chepkwemoi Tengwer; Godfrey Kinyori Wagutu; Henry Kariuki Njeri; Wei Li; Yuan-Yuan Chen; Xiang-Rong Fan (Aquatic Botany, 2025)

Front margin tectonic deformation characteristics of the Xu–Su arc tectonic belt and its tectonic implications - Rong-ying Zheng; Yun-sheng Yao; Jun Shen; Hao-yuan He; Chun-shan Guo; Xiao-hui Yu; Xun-ye Dai; Lu-wei Li; Xuan-kai Jiao; Zhong-yuan Yu; Zhi-tao Gao (Applied Geophysics, 2025)

Two new steroidal saponins from the roots and rhizomes of Helleborus thibetanus - Hao Wei; Xin Zhang; Chao Ding; Yuze Li; Ziqiang Wang; Xiaomei Song; Dongdong Zhang; Rong Lin (Natural Product Research, 2025)

An end-to-end maturity prediction and hierarchical counting method for cherry tomatoes - Jiacheng Rong; Xianjun Li; Wanli Zheng; Tongqiang Chen; Ting Yuan; Pengbo Wang; Wei Li (Biosystems Engineering, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

3,4-seco-Prenyllabdane sesterterpenoids and 3,4-seco-labdane diterpenoids with Zika virus inhibitory potential from Callicarpa nudiflora - Xue-Wen Wu; Guan-Rong Qiao; Xue-Rong Zhao; Qi Li; Muhammad Aurang Zeb; Xiao-Li Li; Chang-Bo Zheng; Wei-Lie Xiao (Phytochemistry, 2025)

Elimination of antibiotic resistance genes and adaptive response of Firmicutes during chicken manure composting - Wei-Li Jia; Ben Wang; Lu-Kai Qiao; Fang-Zhou Gao; Wang-Rong Liu; Liang-Ying He; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

All-weather highly efficient degradation of persistent organic pollutants over RhB-sensitized BiOCl under natural sunlight - Wen Sun; Chunping Su; Wei Zhang; Hui Li; Huiping Zhao; Rong Chen (Journal of Environmental Chemical Engineering, 2025)

Molecular characterization and expression analysis of IL-21 and its four receptor genes in yellow catfish (Pelteobagrus fulvidraco) in response to Edwardsiella ictaluri infection - Zhang-Ping Li; Xin-Xin Jiang; Zi-Rui Tang; Mao-Mao Dong; Ping Jiang; Gui-Rong Zhang; Xu-Fa Ma; Kai-Jian Wei (Fish & Shellfish Immunology, 2025)

A novel multi-dimensional viscoelastic mitigation device: Shake table tests and numerical assessment of precast concrete sandwich wall panel structure - Jia-Xuan He; Zhao-Dong Xu; Zhong-Wei Hu; Lian-Yu Zhang; Qiang-Qiang Li; Yao-Rong Dong; Gabriele Milani (Engineering Structures, 2025)

Surface engineering of copper peroxide nanodots and Au nanozyme on porphyrin-based metal-organic frameworks induces cascade reactions for colorectal cancer treatment - Haoyu Chen; Rong Liu; Jiaxin Fu; Xiaohan Zhang; Xiaohua Zhu; Mingjie Wei; Feng Liu; Peng Yin; Haitao Li; Youyu Zhang; Meiling Liu; Juewen Liu (Chemical Engineering Journal, 2025)

Protective effect of cartilage oligomeric matrix protein (COMP) on osteoarthritis-like chondrocytes based on the nuclear factor kappa B (NF-κB) pathway - Wei Weng; Rong Wu; Zhenguo Sun; Haidong Li; Yuxin Shen; Heng Li; Jikang Min (Journal of Molecular Histology, 2025)

Exploring morphological heterogeneity of circulating tumor cells: machine learning-based approach for cell identification and prognostic implications - Peng-Xiang Wang; Yu-Chen Zhong; Bin Duan; Jian-Wen Cheng; Yun-Fan Sun; Wen-Jing Zheng; Kai-Qian Zhou; Yang Xu; Hai-Xiang Peng; Wei-Xiang Jin; Hai-Min Li; Xiao-Juan Sun; et al. (Science Bulletin, 2025)

PtBi nanocatalysts with controlled chain-like structure and composition: Solvothermal synthesis and ethanol oxidation performance - Luo-Yi Yan; Han-Tao Zhang; Xiao-Yu Lu; Li-Ming Liu; Rong-Hua Zhang; Zheng Cheng; Shuai-Wei Fan; Xin-Wen Zhou (Fuel, 2025)

Reductive dechlorination of 1,1,2-trichloroethane in groundwater by zero valent iron coupled with biostimulation under sulfate stress: Differences and potential mechanisms - Naijin Wu; Yi Li; Yizhou Liu; Yangfan Feng; Wenbo Fei; Tianwen Zheng; Liming Rong; Nan Luo; Yun Song; Wenxia Wei; Peizhong Li (Environmental Research, 2025)

Rapid and efficient nitrogen removal by a novel heterotrophic nitrification-aerobic denitrification bacteria Marinobacterium maritimum 5-JS in aquaculture wastewater: Performance and potential applications - Fu-Rong Wang; Shi-Yu Feng; Shuai Liang; Wei-Yu Du; Long-Qi Wang; Yu-Wei Zhang; Jia-Yu Ren; Shuang Gao; Yu-Jie Zhu; Yu-Ting Cong; Li Wang; Jing Gu; et al. (Environmental Research, 2025)

Seismic behavior of CFST components for shear walls using double corrugated steel plates - Xu Liao; Xian Li; Wei Li; Rong Su; Ming Chen (Engineering Structures, 2025)

A green-solvent processed multifunctional bamboo composite with high strength, robust fire retardancy, and dimensional stability - Xiangyu Ren; Huijun Zhang; Weibing Xue; Tongda Liu; Rong Liu; Xin Ran; Ping Wang; Wei Gao; Yanmei Li; Guanben Du; Long Yang (Chemical Engineering Journal, 2025)

Collaborative mechanism of microbial fuel cell native bacteria and Sporosarcina pasteurii: Improving mineralization performance - Jin-Di Liu; Wei-Min Cheng; Xiang-Ming Hu; Xiao Li; Yue Feng; Yan-Yun Zhao; Ming-Yue Wu; Hui Rong; Xiao-Niu Yu; Yin-Bo Xiang; Zhi-Rong Zhang (Chemical Engineering Journal, 2025)

Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia-bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2025)

Anthropogenic Influence on the Compound Hot and Dry Event in Summer 2022 in the Tibetan Plateau Based on Statistical Downscaling CMIP6 Models - Kening Xue; Wei Li; Siyan Dong; Rong Yu; Leibin Wang (International Journal of Climatology, 2025)
In the summer of 2022, the Tibetan Plateau experienced a record‐breaking compound hot and dry event (CHDE). This study quantifies the contribution of anthropogenic influence to this compound event using a set of high‐resolution statistical downscaling results from six CMIP6 models. The Copula function was used to calculate the joint probability of the compound event. The results show that in the summer of 2022, hot conditions in the Tibetan Plateau broke records since 1961, with a return period of 408 years. The dry conditions were also uncommon, with a return period of 47 years. The hot and dry compound event is particularly rare, with a return period of more than 20,000 years. Based on the results from statistical downscaling models, it was found that anthropogenic influence has increased the risks of dry and hot conditions similar to those in the Tibetan Plateau in 2022 by factors of 3.3 [1.5, 5.2] and 14 [8.6, 21.2], respectively. Additionally, the risk of compound events has been increased by a factor of 46.7 [26.7, 77.6]. In the future, with the intensification of warm‐wet situations on the Tibetan Plateau, the hot conditions similar to 2022 are expected to increase remarkably, with the risk of occurrence rising by factors of 56 [34, 108] and 75 [44, 162] during the periods 2021–2040 and 2051–2070, respectively. Conversely, dry conditions are projected to decrease, with reductions of 0.21 [0.075, 0.46] and 0.51 [0.3, 1.2] times in the two future periods. However, the risk of compound events is expected to increase, with increases of 3.3 [1.5, 5.2] times and 11 [6, 25] times during the two periods. This study is the first to use downscaled simulation to conduct event attribution analysis for the Tibetan Plateau, which can deepen the understanding of the influence of human activities on compound events.

Molecular Insight Into the Hydrolysis of Phthalate Esters by a Family IV Esterase - Zhen Rong; Li‐Guo Hong; Ying‐Yi Huo; Jixi Li; Dao‐Qiong Zheng; Yang Ha; Jeffrey Fan; Xue‐Wei Xu; Yue‐Hong Wu (Environmental Microbiology, 2025)
Phthalate esters (PAEs) are prevalent environmental contaminants, with their biodegradation efficiently driven by microorganisms through ester bond hydrolysis. This study investigates the mechanism of Poc14, a novel family IV esterase, using x‐ray crystallography, bioinformatics, biochemistry and site‐directed mutagenesis. Phylogenetic analysis classifies Poc14 as a family IV esterase with conserved catalytic motifs crucial for its activity. Poc14 retains over 80% activity at 50°C for 4 h and tolerates up to 5% methanol or DMF, though surfactants like Tweens inhibit its function. Poc14 activity is independent of metal ions, and the addition of EDTA further enhances its activity by approximately 130%. The 1.8 Å crystal structure reveals a CAP domain and two substrate channels. Enzyme assays show Poc14 hydrolyses short‐chain diethyl phthalate (DEP) ( K m = 0.068 mM, V max = 9975 μM/min/mg) but not long‐chain di(2‐ethylhexyl) phthalate (DEHP) due to steric hindrance. Molecular docking assessed Poc14's potential to hydrolyse DEP and DEHP after residue mutations, resulting in the Poc14‐AAG variant. Poc14‐AAG could hydrolyse one bond of DEHP and diester bonds of DEP. Our study positions Poc14 as a promising enzyme for environmental remediation, with potential for optimising DEHP degradation and exploring dimerisation effects.

Active spermatogenesis in YY supermale common carp makes it suitable for potential control of this invasive species - Kuangxin Chen; Yi Rong; Yuanqi Guo; Mouyan Jiang; Yulai Wei; Xishuang Shan; Yongming Li; Yanlong Song; Ji Chen; Binbin Tao; Wei Hu (Aquaculture, 2025)

Investigation of antibacterial activity and mechanism of action: Design and synthesis of coumarin derivatives containing sulfonamide groups - Song Bai; Miaohe Zhang; Miao Li; Suran Wan; Fang Wang; Shouyin Tang; Lijun Chen; Xian Wei; Rong Wu (Phytochemistry Letters, 2025)

Size-dependent internalization of polystyrene microplastics as a key factor in macrophages and systemic toxicity - Wei-Qiang Luo; Meng-Ting Cao; Chen-Xuan Sun; Jun-Jian Wang; Meng-Xi Gao; Xue-Rui He; Le-Ning Dang; Yang-Yang Geng; Bing-Yao Li; Jing Li; Zhi-Cheng Shi; Xing-Rong Yan (Journal of Hazardous Materials, 2025)

Climate warming will alter the impact of microplastics on the bioavailability of arsenic in a subtropical estuary - Yue Zeng; Yajie Jiang; Yunqin Li; Xiang Xu; Wei Yu; Rong Yu (Journal of Hazardous Materials, 2025)

The food application of a novel Staphylococcus aureus bacteriophage vB_SA_STAP152 and its endolysin LysP152 with high enzymatic activity under cold temperature - Yuanyu Li; Jingsha Dai; Shi Wu; Dongli Rong; Jiahui Huang; Miao Zhao; Jumei Zhang; Qinghua Ye; Qihui Gu; Youxiong Zhang; Xianhu Wei; Qingping Wu (Food Microbiology, 2025)

Nectar characteristics and pollination ecology of Camellia perpetua in South China - Hai-du Jiang; Dan-juan Zeng; Hui-zhen Qin; Li-hui Peng; Yi-shan Yang; Zong-you Chen; Rong Zou; Jian-min Tang; Yun-sheng Jiang; Zhong-chen Xiong; Xiao Wei; Sheng-feng Chai (Flora, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Microwave-assisted pyrolysis of spent bleaching clay: A study of pyrolysis characteristics, kinetics, and intrinsic mechanism - Bang Yao; Li Chao; Yingwen Zhang; Yang Liu; Chunbao Zhou; Dekai Fan; Yunxiang Li; Pengfei Zhu; Wei Li; Yanran Lin; Lei Gao; Chen Chen; et al. (Chemical Engineering Journal, 2025)

Development of Agro-Based Engineered Biochars for Low Concentration Nitrate Adsorption: Modification Selection, Performance, Factors, Mechanism, and Reliability - Wenjia Han; Ai Chen; Zhuocan Li; Rong Zhou; Kai Zhang; Wei Zhao; Xiaotao Bi; Xiali Zhang (Water, Air, & Soil Pollution, 2025)

Glymphatic Impairment Associated with Neurocognitive Dysfunction in Moyamoya Disease - Chaofan Zeng; Yuanren Zhai; Peicong Ge; Chenglong Liu; Xiaofan Yu; Wei Liu; Junsheng Li; Qiheng He; Xingju Liu; Xun Ye; Qian Zhang; Rong Wang; et al. (Translational Stroke Research, 2025)

Identification and validation of mitochondrial endoplasmic reticulum membrane-related genes in atherosclerosis - Li-Rong Wang; Chun-Xi Zhang; Lv-Bo Tian; Jie Huang; Li-Jun Jia; Hao Tao; Neng-Wei Yu; Bing-Hu Li (Mammalian Genome, 2025)

Mineral fertilizer substitution and application of Bacillus velezensis SQR9 reduced nitrogen-oxide emissions in tropical vegetable fields - Wei Tian; Feilong Liang; Longping Tu; Zhe Xu; Rong Li; Ruoya Ma; Yawen Huang; Shuang Wu; Shuqing Li; Jinyang Wang; Shuwei Liu; Zhaoqiang Han; et al. (Agriculture, Ecosystems & Environment, 2025)

Atmospheric nitrogen deposition has minor impacts on the abundance and diversity of arbuscular mycorrhizal fungi and their contribution to soil carbon stock in tropical forests - Andi Li; Peter Meidl; Senhao Wang; Bo Tang; Matthias C. Rillig; Guangcan Yu; Jing Chen; Rongzhen Liu; Zhiyang Lie; Anchi Wu; Lili Rong; Cheng Peng; et al. (Soil Biology and Biochemistry, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Recent progress in protein-based high internal-phase Pickering emulsions: Composition, stabilization, applications, and future trends - Wei Liang; Xiaofeng Zhan; Pengkai Wang; Chuan Li; Lu Zhang; Jianhua Rong; Ru Liu; Shanbai Xiong; Yang Hu (Food Research International, 2025)

Interfacial clustering-derived fluorescent, mechanically strong and fire-safe epoxy composites - Dong-Qing Zeng; Xin-Miao Li; Feng Chen; Wei-Bin Bai; Yu-Cai Lin; Rong-Kun Jian (Chemical Engineering Journal, 2025)

Iron isotopic fractionation during seafloor hydrothermal alteration of oceanic upper crust, as recorded in Geotimes lavas of Semail ophiolite, Oman - Rong-Zhong Bo; Yildirim Dilek; Wei-Qiang Li; Sobhi Nasir; Peng-Jie Cai; Hui-Chao Rui; De-Hong Du; Shi-Chao An; Yu-Xiao Lu; Hao-Chen Duan; Dong-Yang Lian; Jing-Sui Yang; et al. (Chemical Geology, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Monitoring-based analysis of the responses of upper structure and tunnel lining during shield tunneling with pile cutting - Zhi-Xiong Liu; Xiao-Wei Ye; Ke Song; Ci-Rong Lu; Yue-Jun Song; Xiao-Jun Li; Li-An Zhao (Tunnelling and Underground Space Technology, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Effects of triclosan on microalgal-bacterial symbiosis system operating in stable phase: Performances and mechanisms - Qiang Chao; Tian-Yang Wang; Cong-Cong Tang; Rong Wang; Zhang-Wei He; Zhi-Hua Li; Yu Tian (Journal of Water Process Engineering, 2025)

Simultaneous recovery of water and antiscalant from cooling tower blowdown water by electrodialysis: Mechanism and cost-effectiveness - Jia-Rong Li; Jing-Han Wei; Yu-Chen Jin; Xian-Qiu Zhang; Hai-Ou Song; Ming-Xia Du (Journal of Cleaner Production, 2025)

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

Petrogenesis and age of granitoids associated with the Dongshan Cu polymetallic deposit, East Kunlun Orogenic Belt, NW China: Implications for the Middle to Late Triassic tectonic setting and Cu polymetallic mineralization - Yi-Chen Chen; Zheng-Jiang Ding; Jun-Wei Bo; Shi-Jiong Han; Ting-Ting Li; Pan Ji; Rong-Qiang Guo (Geochemistry, 2025)

Interfacial structure design enables rapid reaction kinetics for high-voltage NCM 613 cathodes - Yuan Xiao; Rong Gu; Tingting Zheng; Bowen Chang; Qiaoxia Li; Shuaiqi Gong; Xin Wei; Qunjie Xu; Yulin Min (Chemical Engineering Journal, 2025)

Construction of phenothiazine-decorated ZnO quantum dots with intelligent response to bacterial pH/amidase microenvironment for inducing bacterial ferroptosis-like death - Wu-Bin Shao; Rong-Shuang Luo; Yan-Wei Huang; Long Cheng; Dan Zeng; Xiang Zhou; Li-Wei Liu; Song Yang (Chemical Engineering Journal, 2025)

Legume intercropping improves soil organic carbon stability in drylands: A 7-year experimental validation - Wei Wang; Meng-Ying Li; Yang Wang; Jian-Ming Li; Wei Zhang; Qin-Hui Wen; Shuang-Jin Huang; Guang-Rong Chen; Shuang-Guo Zhu; Jing Wang; Fazal Ullah; You-Cai Xiong (Agriculture, Ecosystems & Environment, 2025)

Recent advances in the role of gasotransmitters in necroptosis - Meng-Yuan Hao; Hong-Jie Li; Hang-Shen Han; Ti Chu; Yan-Wen Wang; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Apoptosis, 2025)

Observed seasonal evolution and origins of the western Yellow Sea Cold Water Mass - Chuanjie Wei; Xiaohui Tang; Kai Ge; Anqi Xu; Yuanlong Li; Yong Jiang; Zengrui Rong; Fei Yu (Frontiers in Marine Science, 2025)
The Yellow Sea Cold Water Mass (YSCWM) is one of the most prominent hydrological features of the Yellow Sea. As a low-temperature, nutrient-rich subsurface water mass, the YSCWM fundamentally regulates biogeochemical cycles, functions of marine ecosystems, and fishery resources of the YS. In boreal summer, the YSCWM shows a robust triple-core structure, in which the western component, dubbed the “western YSCWM”, is revisited in this study. Through analyzing in-situ observational data collected by research cruises of the Institute of Oceanology, Chinese Academy of Sciences (IOCAS) and Lagrangian tracing experiments based on a high-resolution ocean model, we provide a thorough investigation for seasonal evolution and origins of the western YSCWM. In-situ observations during 2006-2007 and 2014-2015 suggest that the western YSCWM bears a tight connection to the colder coastal waters near the Shandong Peninsula and achieves the coldest temperature in summer. Analysis of model simulations confirms that the cooling of the western YSCWM in spring and summer is caused mainly by southward cold-water transport of the Shandong Coastal Current (SDCC) from the Shandong coasts and the northern Yellow Sea. We also reveal a contribution of the Subei Shoal water via the Subei Coastal Current (SCC) in summer, which plays a critical role in the quick vanishing of the western YSCMW in early autumn. These findings contribute to our understanding of the formation, seasonal evolution, and heat budgets of the YSCWM.

Recombinant probiotic Escherichia coli delivers the polymeric protein of swine influenza virus for protection - Jin-Mei Sun; Wen-Qiang Zhang; Yan-Jin Li; Tian-Kui Guo; Rong-Rong Zhang; Yong-Lei Yang; Ying Zhao; Ling-Jiao Yu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; et al. (Veterinary Microbiology, 2025)

Optimizing nitrogen fertilization and irrigation strategies to balance agroecosystem services in the wheat-maize double cropping system: A 21-year field study - Xinyue Qu; Wei Yao; Huijia Ji; Yi Xu; Rong Jia; Xinjie Chen; Hongjun Li; Antonio Rafael Sánchez-Rodríguez; Yanjun Shen; Yadong Yang; Zhaohai Zeng; Huadong Zang (Field Crops Research, 2025)

Ventral Hippocampal CA1 GADD45B Regulates Susceptibility to Social Stress by Influencing NMDA Receptor-Mediated Synaptic Plasticity - Mengbing Huang; Jian Bao; Xiaoqing Tao; Yifan Niu; Kaiwei Li; Ji Wang; Xiaokang Gong; Rong Yang; Yuran Gui; Hongyan Zhou; Yiyuan Xia; Youhua Yang; et al. (Neuroscience Bulletin, 2025)

Identification of Potential Causal Genes for Neurodegenerative Diseases by Mitochondria-Related Genome-Wide Mendelian Randomization - Kang-Fu Yin; Ting Chen; Xiao-Jing Gu; Zheng Jiang; Wei-Ming Su; Qing-Qing Duan; Xiang-Jin Wen; Bei Cao; Ju-Rong Li; Li-Yi Chi; Yong-Ping Chen (Molecular Neurobiology, 2025)

The effect of soil depth on stoichiometry was greater than that of elevation in Abies georgei var. Smithii forest in Southeastern Tibet, China - Si-jie Zhu; Jiang-rong Li; Bo Zhang; Fang-wei Fu; Liang-na Guo (Acta Oecologica, 2025)

Late Quaternary slip rate of the Northern Margin Fault of the Huaizhuo Basin in the North China Block and its seismological implications - Lu-wei Li; Zhong-yuan Yu; Chun-miao Qiu; Wen-xuan Wang; Qian Zhao; Rong-ying Zheng; Yan-Lin Yang (Applied Geophysics, 2025)

α-asarone activates mitophagy to relieve diabetic encephalopathy via inhibiting apoptosis and oxidative stress - Xiao-dan Yan; Rong-hua Fan; Yu Wang; Xiao-xu Duan; Xuan Wei; Lin-sen Li; Qing Yu (Metabolic Brain Disease, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Advancements in the development of porous nanomaterials for CO2 capture of deep decarbonization: Pore structure and chemical group optimization - Sifan Bao; Xudong Zheng; Zihuai Xu; Biao Ji; Zhouzhou Yang; Wei Sun; Lin Guo; Youming Zhu; Jinfeng Mei; Jian Rong; Zhongyu Li (Journal of Environmental Chemical Engineering, 2025)

Analysis of genetic diversity and population structure of Pinellia ternata using EST-SSR markers - Mingxing Wang; Rong Xu; Ming Luo; Xinyao Li; Lu Wei; Mi Lei; Dahui Liu; Yuhuan Miao (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Amine-impregnated elastic carbon nanofiber aerogel templated by bacterial cellulose for CO2 adsorption and separation - Sifan Bao; Xudong Zheng; Zihuai Xu; Biao Ji; Zhouzhou Yang; Wei Sun; Jinfeng Mei; Jian Rong; Zhongyu Li (Fuel, 2025)

Lipid peroxidation inhibition by icaritin and its glycosides as a strategy to combat iron overload-induced osteoporosis in zebrafish - Chang-Yu Yan; Xiao-Yuan Gu; Shuo-Yan Tan; Ao-Yu Mei; Jiang-Hao Mao; Yi Dai; Jie Niu; Wei-Xi Li; Hiroshi Kurihara; Yi-Fang Li; Rong-Rong He (Food Research International, 2025)

Effect of magnetic field-assisted thawing on the quality and microstructure of Portunus trituberculatus meat - Rong Shi; Zhongqi Sun; Xuemei Yu; Huamao Wei; Gaoshang Li; Wenge Yang (Food Research International, 2025)

Design, synthesis and antifungal activity of novel pyrazole-amide-isothiazole derivatives as succinate dehydrogenase inhibitors - Ai-ling Bao; Xian-song Xie; De-yuan Wang; Zi-quan Deng; Yun Chen; Dan Liu; Wei-yi Li; Xiao-rong Tang; Wei Cheng; Ying-kun Yan (Food Chemistry, 2025)

Inhibition of electron transfer in anaerobic ammonia-oxidized granular sludge by polyethylene terephthalate microplastics and nanoplastics: A new perspective on molecular docking and molecular dynamics simulations - Chaofan Xie; Dongyue Li; Jiarui Li; Linzhu Du; Yanshuo Wu; Rong Luo; Zheng Wang; Jun Li; Yuhan Zhu; Wei Guo (Chemical Engineering Journal, 2025)

PVA-enhanced green synthesis of CMC-based lithium adsorption films - Shengkai Liu; Huiling Li; Xi Li; Wei Wang; Chunguang Rong; Mengjie Yang; Yonggui Wang; Jing Wang; Yabei Xu; Daxin Liang; Yanjun Xie (Carbohydrate Polymers, 2025)

Revealing microbial compatibility of partial nitritation/Anammox biofilm from sidestream to mainstream applications: Origins, dynamics, and interrelationships - Yanxiao Wei; Weizhe Xia; Yunzhi Qian; Chao Rong; Min Ye; Yujie Chen; Jun Kikuchi; Yu-You Li (Bioresource Technology, 2025)

Different contributions of microbial and plant residues to soil organic carbon accumulation during planted forest and abandoned farmland restoration, Loess Plateau, China - Hongjian Hao; Rong Wang; Shicai Li; Duo Pian; Ning Peng; Ahejiang Sailike; Zhouchang Yu; Jiayi Shi; Xingbo Wang; Zihan Wang; Wei Zhang (Plant and Soil, 2025)

Transcriptome Sequencing Reveals Effects of Artificial Feed Domestication on Intestinal Performance and Gene Expression of Carnivorous Mandarin Fish (Siniperca chuatsi) and Related Mechanisms - Jia-Xing Luo; Xiao-Tian Gao; Zhen Rong; Li-Han Zhang; Yan-Feng Sun; Zun-Li Qi; Qi Yu; Khor Waiho; Wei-Xu Zhao; Yi-Huan Xu; Chun-Long Zhao; Cheng-Bin Wu (Marine Biotechnology, 2025)

Soil labile organic carbon and nitrate nitrogen are the main factors driving carbon-fixing pathways during vegetation restoration in the Loess Plateau, China - Yujie Liang; Rong Fu; Ahejiang Sailike; Hongjian Hao; Zhouchang Yu; Rong Wang; Ning Peng; Shicai Li; Wei Zhang; Yangyang Liu (Agriculture, Ecosystems & Environment, 2025)

Analysis of factors influencing microseismic detection and location in shale gas extraction areas of western Hubei - Wan-peng Hao; Li-fen Zhang; Yan-nan Zhao; Rong-ying Zheng; Wei-bing Qin; Jing-gang Li (Applied Geophysics, 2025)

Performance prediction of urban tunnel purification system based on the verified random number screening algorithm - Jie Xia; Hao-Yi Zhao; Hui Ren; Long Chen; Fang Li; Wei-Rong Shi; Yi-Song Xie; Mei-Lan Tan; Fei Li; Bin Zhou (Sustainable Cities and Society, 2025)

Geothermal distribution and evolution of fault-controlled Linyi geothermal system: Constrained from hydrogeochemical composition and numerical simulation - Yuzhong Liao; Wei Zhang; Yuwei Rong; Long Li; Guoqing Hu (Geothermics, 2025)

Weavable composite filament for sustained electricity generation from multiple sources - Rong Liu; Haoyu Li; Zhenzhou Fu; Hailou Wang; Jiamu Dai; Kai Dong; Ick Soo Kim; Wei Zhang (Chemical Engineering Journal, 2025)

Characterization of Gut Microbiota in Rats and Rhesus Monkeys After Methamphetamine Self-administration - Li He; Jia-hui Zhou; Huan Li; Wen-lei Zhang; Tie-qiao Liu; Hai-feng Jiang; Rong-wei Zhai; Xiao-jie Zhang (Molecular Neurobiology, 2025)

Intermittent fasting shifts the diurnal transcriptome atlas of transcription factors - Min Fu; Siyu Lu; Lijun Gong; Yiming Zhou; Fang Wei; Zhigui Duan; Rong Xiang; Frank J. Gonzalez; Guolin Li (Molecular and Cellular Biochemistry, 2025)